Investigating the Integration of Sustainability in Physics Education: Teacher Perceptions and Student Motivation in UAE Secondary Schools - Al Neyadi , Saif; Alzyoudi , Mohammed (Journal of Posthumanism, 2025)
This study examines how sustainability is integrated into the secondary physics curriculum in the UAE, focusing on teachers' perceptions, curricular coverage, and student motivation. Using a mixed-methods approach, surveys were conducted with 200 physics teachers and 250 secondary students in Al Ain. The results showed that while teachers recognize the importance of sustainability, its coverage in the curriculum is limited. Teachers reported moderate confidence in teaching sustainability topics, emphasizing the need for professional development. Students demonstrated strong awareness of sustainability issues, high motivation to engage in related activities, and an understanding of physics' relevance to environmental challenges. The study highlights the need for curricular reforms in UAE secondary education, professional development for teachers, and the integration of interdisciplinary and active learning approaches to foster critical thinking and environmental responsibility. These steps will help prepare students to address both local and global sustainability challenges effectively.